Information technologies and training facilities at Zaporizhzhia state medical university - Sharavara, L. P.; Шаравара, Лариса Павлівна (Poland: Warsaw, 2018)
Abstract. The article describes the features of the use of innovative technologies in the educational process of the Zaporizhzhia State Medical University. The purpose of innovative technologies in the educational process is noted. The main types of innovative technologies embedded in the educational-pedagogical process, namely the Moodle system and the system of distance learning of students and applicants of Zaporizhzhia State Medical University, are listed. The goals and benefits of innovative education are given. It has been established that the use of innovative teaching tools significantly improves the efficiency of teaching, allows to improve the educational process, increase students' interest in learning, and prepare the young generation for life in the information society.
Keywords: innovative teaching methods; distance learning; education